MR Angiography at 3T versus Digital Subtraction Angiography in the Follow-up of Intracranial Aneurysms Treated with Detachable Coils - Majoie, Charles B. L. M. (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Digital subtraction angiography (DSA) is used to follow-up intracranial aneurysms treated with detachable coils to identify recurrence and determine need for additional treatment. However, DSA is invasive and involves a small risk of neurologic complications. We assessed the feasibility and usefulness of 3D time-of-flight (TOF) MR angiography (MRA) performed at 3T compared with DSA for the follow-up of coil-treated intracranial aneurysms. METHODS: In a prospective study, 20 consecutive patients with 21 intracranial aneurysms treated with coils underwent DSA and nonenhanced and enhanced multiple overlapping thin-slab acquisition 3D TOF MRA at 3T on the same day at a mean follow-up of 6 months (range, 4–14 months) after coil placement. MRA images were evaluated for presence of artifacts, presence and size of aneurysm remnants and recurrences, patency of parent and branch vessels, and added value of contrast material enhancement. MRA and DSA findings were compared. RESULTS: Interobserver agreement of MRA was good, as was agreement between MRA and DSA. All three recurrences that needed additional treatment were detected with MRA. Minor disagreement occurred in four cases: three coil-treated aneurysms were scored on MRA images as having a small remnant, whereas on DSA images these aneurysms were occluded; the other aneurysm was scored on MRA images as having a small remnant, whereas on DSA images this was a small recurrence. Use of contrast material had no additional value. Coil-related MR imaging artifacts were minimal and did not interfere with evaluation of the occlusion status of the aneurysm. CONCLUSION: High-spatial-resolution 3D TOF MRA at 3T is feasible and useful in the follow-up of patients with intracranial aneurysms treated with coil placement.